Madrasah as the Central Educational Institutions during the Abbasid Era - Lubis, Zahra Albaturrizkiyah; Siregar, Oki Oktapiani; Nasution, Abdusima (STIT Ahlussunnah Bukittinggi, 2025)
This article critically analyzes the madrasah as a central institutional apparatus in the formation and development of Islamic education during the Abbasid period. Rather than functioning merely as sites of knowledge transmission, madrasahs operated as epistemic and socio-political institutions that shaped intellectual authority, religious orthodoxy, and social stratification. Employing a qualitative library research design, this study conducts a critical historiographical analysis of classical and contemporary sources. The findings reveal that, particularly through the Nizamiyyah Madrasah, the Abbasid educational system underwent a process of institutional consolidation marked by curriculum standardization, the integration of revealed (naqli) and rational (ʿaqli) sciences, and the professionalization of pedagogical practices. Moreover, madrasahs functioned as mechanisms of ideological reproduction, contributing to the consolidation of Sunni orthodoxy and the stabilization of Abbasid political authority. This study argues that the Abbasid madrasah represents a foundational model for the structural and epistemological configuration of formal Islamic education, offering enduring theoretical implications for contemporary Islamic educational institutions.